Eksplorasi Gerak Bantengan: Meningkatkan Keterampilan Motorik Kasar Anak - Azizah, Nuril; Wijayanti, Rina; Anggraini, Henni (Golden Age: Jurnal Pendidikan Anak Usia Dini, 2025)
This study aimed to examine the effect of traditional Bantengan dance movements on improving gross motor skills among Group A early childhood students. The research employed a Classroom Action Research (CAR) design based on the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection stages conducted over two cycles. The subjects were 14 Group A students at TK DWP 1 Pandansari in the 2024/2025 academic year. The findings indicated that children’s gross motor skills improved from 15% in the first meeting of Cycle I to 58% in the second meeting. In Cycle II, the average achievement increased to 78% in the first meeting and 90% in the second meeting. These results demonstrate a gradual and significant improvement in gross motor skills across each cycle. Therefore, the exploration of Bantengan movements proved to be effective in enhancing gross motor skills among early childhood students in Group A.